Characterization of ZnSe nanocrystals grown by vapor phase epitaxy - Tishchenko, V.V.; Kovalenko, A.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
This paper reports the application of scanning electron microscopy, x-ray diffraction, and photoluminescence techniques for characterization of ZnSe nanocrystals grown on GaAs (100) substrate from the vapor phase. The applied characterization techniques show the evidence for coexistence of two sets of nanocrystals with rather different characteristic sizes. In addition, the lowest energy levels of spherically shaped nanocrystals are calculated in the framework of the effective-mass approximation and compared with photoluminescence data.